Street design towards safe city: snatch theft hotspot area / Anith Nabilah Mustafa - Mustafa, Anith Nabilah (2019)
Malaysia is one of the countries in the world that is having rapid urbanisation development. The urban areas tend to have the tendency of having high crime rates because both crime and urban are correlated with each other. There has been a growing concern in towards street pattern design that are safe friendly to all users due to the streets environment which are perceived as street crime prone such as snatch theft to the street users. Snatch theft is one of major street crime problems in Malaysia. The aim of this research is to identify the street pattern in urban area that influence snatch theft activities and the relationships of the street design and snatch theft hotspot areas. The research employed a qualitative methodology using a case study approach. This research is using the Geographic Information System (GIS) and Batchgeo software to produce the snatch theft maps from the statistical data obtained from Royal Malaysian Police (RMP). Taman Pandan Indah neighbourhood in Ampang Jaya was selected based on the statistical data and produced maps of snatch theft from 2010 to 2015. A field observations is conducted using checklists, photos and maps procedures.